2017
DOI: 10.3324/haematol.2017.170381
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived anti-β2GP1 antibodies recognize a peptide motif pattern and not a specific sequence of residues

Abstract: Antiphospholipid antibody syndrome is an autoimmune disease characterized by the presence of so-called antiphospholipid antibodies and clinical manifestations such as recurrent thromboembolic or pregnancy complications. Although the main antigenic determinant for antiphospholipid antibodies has been identified as the β-2-glycoprotein 1 (β2GP1), the precise epitope recognized by antiphospholipid antibodies still remains largely unknown. In the study herein, we wanted to identify a sequence in domain I of β2GP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…A second group (42) also demonstrated an immunodominant T cell epitope within Domain I of β2GPI, in this case in PBMCs of 9 patients with APS (primary or secondary not specified). Five of the 9 patients had a thrombotic event, while the remaining 4 had fetal loss.…”
Section: β2gpi-reactive T Cells In Aps and Slementioning
confidence: 75%
See 1 more Smart Citation
“…A second group (42) also demonstrated an immunodominant T cell epitope within Domain I of β2GPI, in this case in PBMCs of 9 patients with APS (primary or secondary not specified). Five of the 9 patients had a thrombotic event, while the remaining 4 had fetal loss.…”
Section: β2gpi-reactive T Cells In Aps and Slementioning
confidence: 75%
“…APS, anti-phospholipid syndrome; SAPS, secondary APS; SLE, systemic lupus erythematosus. The numbering of amino acids in the studies by Salem et al (40, 41) and de Moerloose et al (42) includes the 19-amino acid leader sequence. In studies by Salem et al (40, 20), murine T cells were derived from spleen.† Prominent HLA restrictions are noted here, but additional restrictions were found; , HLA restriction was not defined .…”
Section: β2gpi-reactive T Cells In Aps and Slementioning
confidence: 99%
“…The mechanism responsible for generating a β2GPI T cell epitope that is shared not only between spontaneous and induced SLE, but also across MHC class II haplotypes remains to be determined. In APS, de Moerloose et al 26 demonstrated an immunodominant T cell epitope in domain I of β2GPI and related it to anti-β2GPI antibody-binding motifs that could be shared among individuals with different MHC class II haplotypes. Currently, there is a paucity of knowledge about common T cell epitopes shared across MHC class II haplotypes in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the light of recent work by de Moerloose et al . , specific amino acid sequences might be less important than structural motifs in the molecule. Furthermore, we cannot exclude the possibility that there might be minor differences between domain‐1 antibodies and anti‐β 2 GPI binding to other domains that we may have overlooked.…”
Section: Discussionmentioning
confidence: 99%